Analysis of association of -174G/C interleukin 6 polymorphism and therapeutic response to methotrexate in rheumatoid arthritis - Joksimović Anastasija; Khouri Christina; Jekić Biljana (Medicinski Podmladak, 2018)
Introduction: Rheumatoid arthritis (RA) is a systemic autoimmune disease with IL-6 as a main mediator of systemic and localized inflammation. The most often used drug for the treatment of RA is methotrexate (MTX). Aim: To explore if there is an association between the 174G/C polymorphism in IL6 gene and response to methotrexate therapy in RA patients. Materials and Methods: Study has included 131 RA patients treated and followed at the Institute of Rheumatology in Belgrade. Clinical response to the MTX therapy was conducted following the EULAR response criteria. Each patient's DNA was isolated by salting-out method. For each patient IL6 174G/C polymorphism genotype was determined by allele specific PCR method. For statistical analyses we have used SPSS program version 17.0. Results: According to EULAR response criteria 103 (78.6 %) patients were responders 12(9.2 %) good and 91 (69.5 %) moderate response) and 28 (21.4 %) were non responders. Among all patients in 47 (35.9 %) we have detected GG genotype, in 69 (52.7 %) GC genotype and in 15 (11.5 %) CC genotype. We have observed no association between genotypes or alleles and response to MTX therapy. Conclusion: No association of -174G/C IL-6 polymorphism and therapeutic response to MTX in RA patients in Serbian population was observed.